Relative deprivation and individual well-being - Xi Chen (IZA World of Labor, 2015)
People who are unable to maintain the same standard of living as others around them experience a sense of relative deprivation that has been shown to reduce feelings of well-being. Relative deprivation reflects conditions of worsening relative poverty despite striking reductions in absolute poverty. The effects of relative deprivation explain why average happiness has been stagnant over time despite sharp rises in income. Consumption taxes on status-seeking spending, along with official and traditional sanctions on excess consumption and redistributive policies may lessen the negative impact of relative deprivation on well-being.
Keywords: I14; I32; Z18; D62; D78; D63; 330; relative status; relative poverty; relative deprivation; health; happiness; well-being